Evaluating Service Quality and Motivation in Affecting Employee Performance in Public Sector - Suryani, Lilis; Kurhayadi, Kurhayadi; Susniwati, Susniwati (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2023)
All members of the institution must actively contribute through excellent work, recognizing that the overall organizational effectiveness hinges on individual employee performance. This research seeks to explore and assess how service quality and motivation impact the job performance of employees in the Banquet Affairs division of the West Java Provincial Government's Regional Secretariat. Employing a quantitative approach, the study employs both descriptive and verification methods to analyze these influences. The population in this study is 30 respondents chosen using the saturated sample method, thus the population is as large as the number of research samples. The data is collected by distributing questionnaire directly towards the respondents, and then it is analyzed using the multiple linear regression method. The research findings state that service quality and motivation partially and simultaneously influences employee performance in the Banquet Affairs of the Regional Secretariat of the West Java Provincial Government. The contribution of service quality and motivation to employee performance is 74.3%.